2011
DOI: 10.1001/archinternmed.2011.30
|View full text |Cite
|
Sign up to set email alerts
|

Medical Device Recalls and the FDA Approval Process

Abstract: Most medical devices recalled for life-threatening or very serious hazards were originally cleared for market using the less stringent 510(k) process or were considered so low risk that they were exempt from review (78%). These findings suggest that reform of the regulatory process is needed to ensure the safety of medical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
159
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 2 publications
4
159
4
2
Order By: Relevance
“…Sometimes when there are apprehensions regarding safety and effectiveness, the FDA can demand clinical data for 510(k) clearance. 6,7,11 What is PMA process? PMA is a process of review to assess the safety and efficacy for all class III devices.…”
Section: What Is Premarket Notification 510(k) Process?mentioning
confidence: 99%
“…Sometimes when there are apprehensions regarding safety and effectiveness, the FDA can demand clinical data for 510(k) clearance. 6,7,11 What is PMA process? PMA is a process of review to assess the safety and efficacy for all class III devices.…”
Section: What Is Premarket Notification 510(k) Process?mentioning
confidence: 99%
“…Yet, these two cases highlight only a fraction of the burgeoning increase in medical device safety alerts 3 and problems with device recalls, and are leading to a rethink of the systems for regulatory approval in both Europe and the USA. 4 Therefore, having an understanding of medical device regulation is now an important requirement for doctors and healthcare professionals alike. To aid this, French-Mowatt and colleagues summarize the current medical device regulation in Europe, 5 outlining the current requirements for CE regulation.…”
mentioning
confidence: 99%
“…Of all medical devices, about half fall in Class I classification, while 45-50% are in Class II, and 5-10% in Class III (Yock, Zenios et al 2015 The 510(k) provision was initially intended for Class I and many Class II devices that did not require significant scientific study. However, the technological evolution quickly increased device complexity, and the FDA lacked necessary resources to modify performance standards for these evolving devices or pass more devices through the rigorous PMA pathway (Zuckerman, Brown et al 2011 (Zuckerman, Brown et al 2011). Further, 12% of the recalled devices that had undergone 510(k) clearance were marketed for "risky or life-sustaining Class III indications," and, as such, should have been legally mandated for review under PMA regulations (Zuckerman, Brown et al 2011).…”
Section: Medical Device Regulationmentioning
confidence: 99%
“…However, the technological evolution quickly increased device complexity, and the FDA lacked necessary resources to modify performance standards for these evolving devices or pass more devices through the rigorous PMA pathway (Zuckerman, Brown et al 2011 (Zuckerman, Brown et al 2011). Further, 12% of the recalled devices that had undergone 510(k) clearance were marketed for "risky or life-sustaining Class III indications," and, as such, should have been legally mandated for review under PMA regulations (Zuckerman, Brown et al 2011). The study revealed differences in the approval criteria for high risk and life sustaining devices and the recall criteria that deems a device life threatening.…”
Section: Medical Device Regulationmentioning
confidence: 99%
See 1 more Smart Citation